The Effectiveness of English Songs to Improve Students' Speaking Skills by Using Problem-Based Learning Methods in Grade XIth Students at SMKS 1 Tamansiswa Pematangsiantar - Sinurat, Nita Utami; Raja, Julita Lumban; Siadari, Maretta Kesya; Doloksaribu, Dominique Sandra; Silalahi, Dumaris (Innovative: Journal Of Social Science Research, 2025)
Speaking is one of the skills that students must have to be able to communicate confidently, exchange ideas, gather information, and share information with others. However, many students face challenges in improving their vocabulary through traditional teaching methods. The gap that this study aims to fill is the lack of research focusing on the effectiveness of English songs using problem-based learning methods in learning strategies to improve speaking skills at the senior high school level. While there is a growing body of research on speaking learning in general, there is limited evidence on students' specific challenges in speaking English. This study aims to determine the effect of English songs using problem-based learning methods in students' speaking mastery in class XI at SMK Swasta 1 Tamansiswa Pematangsiantar. This study uses quantitative methods in collecting data with an experimental design (single group). The results showed a significant increase in the experimental post-test scores, with a t-test value of 12.58, exceeding the critical value of 1.697 at the 0.05 significance level. The findings suggest that English songs significantly enhance speaking learning among students. The study concludes that incorporating interactive and engaging methods such as English songs can effectively improve English speaking skills.